Pharmacokinetics of Nuciferine and N-Nornuciferine, Two Major Alkaloids From Nelumbo nucifera Leaves, in Rat Plasma and the Brain - Ye, Lin-Hu; He, Xiao-Xi; You, Chang; Tao, Xue; Wang, Li-Sha; Zhang, Meng-Di; Zhou, Yun-Feng; Chang, Qi (Frontiers in Pharmacology, 2018)
The leaf of the lotus (Nelumbo nucifera) is a kind of natural plant resource used as both food and herb medicine (He-Ye) in China. Alkaloids are considered the major bioactive compounds of the herb and exhibit various biological activities, including anti-hyperlipidemia, anti-obesity, anti-inflammatory and anti-hyperuricemic effects. Nuciferine (NF) and N-nuciferine (N-NF) are two major alkaloids in the herb. In the present work, the plasma and brain pharmacokinetics of the two compounds were investigated after oral and intravenous (i.v.) administration of a lotus leaf alkaloid fraction to SD rats, by using UPLC-PDA method and brain microdialysis. After oral dose (50 mg/kg), the two compounds NF and N-NF were rapidly absorbed into the blood and reached a mean maximum concentration (Cmax) of 1.71 µg/mL at 0.9 h and 0.57 µg/mL at 1.65 h, respectively. After i.v. dose (10 mg/kg), NF and N-NF were found to have a relatively wide volume of distribution (Vd,λz, 9.48 and 15.17 L/kg, respectively) and slow elimination half-life (t1/2,λz, 2.09 and 3.84 h, respectively). The oral bioavailability of NF and N-NF was estimated as 58.13% and 79.91%, respectively. After i.v. dose (20 mg/kg), the two compounds could rapidly cross the blood-brain barrier and reached their Cmax (in unbound form) of 0.32 and 0.16 µg/mL at 0.89 and 1.22 h, respectively. Both alkaloids had widespread distribution in the brain, with Vd,λz/F values of 19.78 L/kg and 16.17 L/kg, respectively. The mean t1/2, λz values of NF and N-NF in the brain were 1.24 and 1.39 h, respectively. These results can help us to better understand the characteristics and neuro-pharmacological effects of the lotus alkaloid fraction.